Comparison between 18F‐DCFPyL PET and MRI for the detection of transition zone prostate cancer. Issue 16 (13th September 2021) - Liu, Yachao; Dong, Yanliang; Liu, Jiajin; Zhang, Xiaojun; Lin, Mu; Xu, Baixuan
Abstract: Background: We aimed to compare the diagnostic performance of 18 F‐DCFPyL positron emission tomography (PET) and multiparameter magnetic resonance imaging (mp‐MRI) in detecting transition zone (TZ) prostate cancer (PCa). Methods: This retrospective study included 20 patients who underwent 18 F‐DCFPyL PET/MRI and 32 patients who underwent 18 F‐DCFPyL PET/CT and MRI from January 2019 to June 2020. All patients had TZ lesions and underwent prostate biopsies. One senior (reader 1) and one junior (reader 2) nuclear medicine physician evaluated each TZ lesion independently, according to the molecular imaging prostate‐specific membrane antigen scoring system and the Prostate Imaging Reporting and Data System version 2.1 (PI‐RADS v2.1). The histologic diagnosis of prostate biopsy was used as the reference standard. The diagnostic performance of the two methods was compared in terms of inter‐reader agreement and area under the receiver operating characteristic (AUC‐ROC) curve. Results: Of the 52 patients, 43 had TZ PCa. For inter‐reader agreement, the kappa value was 0.883 for 18 F‐DCFPyL PET and 0.393 for mp‐MRI. For PET, both readers had the same diagnostic sensitivity, specificity, and accuracy of 93.0%, 77.8%, and 90.4%, respectively. For mp‐MRI, the diagnostic sensitivity, specificity, and accuracy was 67.4%, 33.3%, and 61.5% for reader 1, and 51.2%, 44.4%, and 51.9% for reader 2, respectively. PET outperformed mp‐MRI for both readers with an AUC of 0.872 for PET versus 0.584 for mp‐MRI, p = .0209 for reader 1, and an AUC of 0.860 for PET versus 0.505 for mp‐MRI, p = .0213 for reader 2. Among the 43 patients with TZ PCa, 18 F‐DCFPyL PET detected a distant bone metastasis missed by the CT in one case and two small lymph node metastases missed by the CT and MRI in another case. Conclusions: These results suggest that 18 F‐DCFPyL PET, which was almost independent of the experience of the readers, was more objective in the evaluation of TZ lesions, and had higher diagnostic value than mp‐MRI.